Plan estratégico de la empresa de helados Fruti-Deli para los años 2022 a 2026 (2021)
Through the deductive methodology, this paper aims to identify each of the essential factors that allow to mitigate threats and take advantage of opportunities, which stimulate growth, the achievement of sustainability in the market and the success of the organisation.